Perancangan Antena Implan pada Frekuensi MICS (Medical Implant Communication Service) Band Untuk Aplikasi Biomedis - Nafisyah Apriani; Yusnita Rahayu; Teguh Praludi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Microstrip antenna is a sensor and monitoring technology that is currently developing rapidly. In the medical field, microstrip antennas have been widely used. This study presents an implantable microstrip antenna that is implanted in the human body for medical applications. The antenna is designed to work in the MICS frequency band (402-405 MHz) using Roger RT Duroid 6010 substrate material (εr = 10.2 and thickness 0.635 mm). The implanted antenna is designed using a spiral miniaturization technique with a radius of 6.74 mm to maintain its dimensions at low frequencies. The implant antenna was simulated using a phantom (skin, fat, muscle) using the CST Studio Suite simulation software. From the simulation results, the return loss value is -17.794, the gain directivity achieved is -47.71 dBi and the VSWR achieved is 1.2619 and the bandwidth is 136.95 MHz. All parameters are in accordance with ITU standardization.Keywords: implanted antenna, MICS band, miniaturization technique, phantom